Outbreak control and clinical, pathological, and epidemiological aspects and molecular characterization of a bovine herpesvirus type 5 on a feedlot farm in S(a)over-tildeo Paulo State - Megid, Jane [UNESP]; Vicente, Acácia Ferreira [UNESP]; Appolinario, Camila Michele [UNESP]; Allendorf, Susan Dora [UNESP]; Mioni, Mateus de Souza Ribeiro [UNESP]; Baraldi, Thas Gasparini [UNESP]; Cortez, Adriana; Heinemann, Marcos Bryan; Fonseca, Clovis Reinaldo Silva [UNESP]; Pelícia, Vanessa Cristina [UNESP]; Ribeiro, Bruna Leticia Devidé [UNESP]; Okuda, Liria Hiromi; et al. (Hindawi Publishing Corporation, 2015)
This paper describes the control, epidemiological, pathological, and molecular aspects of an outbreak of meningoencephalitis in calves due to bovine herpesvirus 5 at a feedlot with 540 animals in Sa (a) over tildeo Paulo State, Brazil. The introduction of new animals and contact between the resident animals and the introduced ones were most likely responsible for virus transmission. Bovine herpesvirus 1 vaccine was used, resulting in the efficacy of the outbreak control, although two bovine herpesvirus 1 positive animals, vaccinated and revaccinated, presented meningoencephalitis, thereby characterizing vaccinal failure.